STUDENTS’ DIFFICULTIES IN READING COMPREHENSION ON REPORT TEXT - Fatin Nadifa Tarigan (BAHAS, 2021)
Abstract This study is aimed to find out the students’ difficulties in reading comprehension on report text. This study was conducted at Universitas Pembinaan Masyarakat Indonesia by using qualitative design. The subject of the study was the students at English Education Study Program in academic year of 2020/2021 consist of 21 students. Test and interview were used in collecting the data. The test was used to take the data of the students’ level in reading comprehension, whereas the interview used to analyze the students’ difficulties on reading comprehension. The data were analyzed by using Miles and Huberman’s theory (2014) using data condensation, data display, and drawing conclusion. The findings revealed that the most of students in academic year of 2020/20121 had some difficulties when reading comprehension and the most difficulty in reading is finding inference meaning. For the average category/level reading comprehension of students at English Education Study Program is in the level of literal reading comprehension. Keywords : Difficulties, Reading Comprehension, Report Text